ISOLATION OF FUNGI FROM THE GASTROINTESTINAL TRACT OF INDIGENOUS CHICKEN - Yudiarti, T.; Yunianto B.I., V.D.; Murwani, R.; Kusdiyantini, E. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
Gastrointestinal tract of chicken is a place in which many kinds of fungi can be found. The aim ofthe research was to isolate fungi from the gastrointestinal tract of the indigenous chicken (AyamKampung). The chicken samples were four days, one week and two months old and were sampled fromchicken farm located in Yogyakarta. Potato dextrose agar (PDA) medium was used to grow the fungi.Fifty pure isolates of fungi were found from three different ages, those were four days, one week andtwo months old chicken were 5, 10 and 35 isolates respectively. The largest number of isolate was foundin ileum, then followed by caecum, jejenum and duodenum. The fifty isolate of fungi belonged to sevenspecies, those were Aspergillus fumigatus, Aspergillus niger, Chrysonilia crassa, Mucor circinelloides,Mucor sp, Rhizopus oligosporus and Rhizopus oryzae.